An Analysis Indonesian-English Code Switching in Lulu Anggriani's Selected Vlogs - I Gusti Bagus Wahyu Nugraha Putra; Putu Devi Maharani; Ni Luh Putu Indra Suardani (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
Abstract In this globalization era, the phenomena of code switching become an object of sociolinguistics which relates to use of two or more languages in daily conversation. This study concerned on analyzing the types and the functions of code switching in Lulu Anggriani’s selected vlogs. The theory proposed by Appel and Muysken (2006) was used to analyzed the types of code switching, and supported by Poplack (1980). The functions of code switching were analyzed by using the theory from Appel and Muysken (2006). The data were analyzed by qualitative method, and the method applied in presenting the data were formal and informal method As the result, this study shows the most dominated types of code switching is inter-sentential switching since the speaker is a fluent bilingual speaker who mostly like to switch the language between sentences. Phatic function is dominant function in Lulu Anggriani’s selected vlogs since the speaker like to give any emphasizing in every utterance that considered as important things. Keywords: vlog, types, functions. Abstrak Pada era globalisasi ini, fenomena alih kode menjadi objek sosiolinguistik yang berkaitan dengan penggunaan dua bahasa atau lebih dalam percakapan sehari-hari. Penelitian ini bertujuan untuk menganalisis jenis dan fungsi alih kode vlog pilihan pada Lulu Anggriani. Teori yang dikemukakan oleh Appel dan Muysken (2006) digunakan untuk menganalisis jenis-jenis alih kode, dan didukung oleh Poplack (1980). Fungsi alih kode dianalisis dengan menggunakan teori dari Appel dan Muysken (2006). Data dianalisis dengan metode kualitatif, dan metode yang digunakan dalam penyajian data adalah metode formal dan informal. Hasil penelitian ini menunjukkan bahwa jenis alih kode yang paling mendominasi adalah inter-sentential switching karena penuturnya adalah penutur dwibahasa yang fasih yang sebagian besar suka mengganti bahasa antar kalimat. Phatic function merupakan fungsi yang dominan pada vlog pilihan Lulu Anggriani karena penutur suka memberikan penekanan dalam setiap tuturan yang dianggap penting. Kata kunci: vlog, jenis, fungsi.